Tinjauan Kesiapan Penyusunan Laporan Keuangan sesuai SAK EMKM pada UMKM di Banyuwangi - Novilia Kareja; Nurul Alfiyah; Dani Agung Wicaksono (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This research was conducted with the aim of getting an overview of the readiness of MSMEs in Banyuwangi to prepare financial reports according to SAK EMKM. This review of MSME readiness is carried out on several aspects, namely the ability to fulfill characteristics, the level of ability to fulfill basic assumptions, and the basis for measurement. This is descriptive research using a qualitative methodology. Respondents in this study were tenants assisted by the Banyuwangi State Polytechnic Business Incubator. The results of this study show that based on the level of ability to fulfill the basic assumptions, it is known that the level of ability is still very minimal. Of the three basic assumptions needed in preparing financial reports according to SAK-EMKM, only the basic assumption of business continuity can be fulfilled by all respondents. Meanwhile, the accrual basis and business entities are still not optimally applied by some SMEs.